2016
DOI: 10.3389/fphys.2016.00212
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 Gene-1562C>T Gene Polymorphism and Coronary Artery Disease in the Chinese Han Population: A Meta-Analysis of 5468 Subjects

Abstract: Background: Multiple studies indicate that the matrix metalloproteinase-9 (MMP-9)-1562C>T gene polymorphism may be associated with an increased risk of coronary artery disease (CAD) in the Chinese Han population. However, a clear consensus has yet to be established.Objective and methods: A meta-analysis of 5468 subjects from 10 separate studies was performed to explore the possible relationship between the MMP-9-1562C>T gene polymorphism and CAD within the Chinese Han population. Pooled odds ratio (ORs) for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In 2016, a metaanalysis was conducted on 10 case-control studies to assess the possible relationship between the MMP-9 (C1562T) SNP and CAD in the Chinese Han population. This study indicated that all genetic comparisons of the MMP-9 (C1562T) SNP increased the risk of CAD in the Chinese Han population [70]. In the current meta-analysis, association between SNPs of the MMP-9 gene family, including MMP-9 (C1562T), MMP-9 (R279Q), MMP-9 (P574R), and MMP-9 (R668Q) polymorphisms and risk of CAD was evaluated.…”
Section: Discussionmentioning
confidence: 93%
“…In 2016, a metaanalysis was conducted on 10 case-control studies to assess the possible relationship between the MMP-9 (C1562T) SNP and CAD in the Chinese Han population. This study indicated that all genetic comparisons of the MMP-9 (C1562T) SNP increased the risk of CAD in the Chinese Han population [70]. In the current meta-analysis, association between SNPs of the MMP-9 gene family, including MMP-9 (C1562T), MMP-9 (R279Q), MMP-9 (P574R), and MMP-9 (R668Q) polymorphisms and risk of CAD was evaluated.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, environmental factors such as diet, smoking, diabetes, and metabolism diseases also play significant roles in CAD development. The microeffects of many other genes relating to CAD development have yet to be fully understood (i.e., matrix metalloproteinase-9 gene-1562C>T polymorphism, TGF- β 1 gene−509C/T Polymorphism) ( 33 , 34 ). PCSK9 gene D129G, S127R, R496W, and R218S polymorphisms also influence the PCSK9 activity and CAD susceptibility ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also investigated the association between MMP-9 gene and CAD. Zhang et al 22 provided evidence that rs3918242 polymorphism may have modification effects on CAD susceptibility in Asians, but another meta-study 23 suggested that the MMP-9-rs3918242 was associated with an increased CAD trend in Chinese Han population. Therefore, the Han Chinese-1562T carriers may increase the risk of CAD.…”
Section: Discussionmentioning
confidence: 99%